Vascular flora of the cerrado of Bauru-SP - Cavassan, Osmar [UNESP]; Weiser, Veridiana de Lara [UNESP] (Revista Biota Neotropica, 2015)
Information on the cerrado vascular flora of the municipality of Bauru has been provided in lists of floristic surveys carried out in fragments of this vegetation type at different times, applying different criteria, and conforming to current taxonomic classifications. We organized this information according to APG III and revised synonymies, aiming at producing a single floristic list of species occurring in cerrado sensu lato or ecotonal areas (transitions between cerrado and seasonal forest) in municipality of Bauru to inform conservation proposals. For this purpose, we referred to all floristic lists of vascular plants found in cerrado fragments in Bauru and to botanic material collected and deposited in the herbaria of the Department of Biological Sciences, School of Sciences, Bauru Campus, UNESP (UNBA), and of the Bauru Botanical Garden (JBMB). We recorded 371 species from 78 families. Fabaceae was the richest in species. We also indicated each mentioned species' habit and the vegetation types where plants occur in the municipality.
Keywords: floristics; savanna; plant survey